Mini-channel cooling system for solar PV Panels with hybrid magnetic nanofluid and magnetic field - Suvanjan Bhattacharyya; Naman Jain; Tapasvi Bhatt; Humaira Yasmin; Mohsen Sharifpur (Results in Engineering, 2023)
This study delves into the interplay between magnetic fields, heat transfer, and fluid behavior within a 3D mini-channel. Exploring the effects of a magnetic field on a hybrid nanofluid (Fe3O4–TiO2) under varying intensities (1000–2000 Gauss) and positions. Using numerical simulations (finite volume method), key parameters like Nusselt number (Nu), Friction factor (f), and Thermal Enhancement Factor (TEF) have been analyzed to uncover how magnetic fields and nanofluids interact in complex geometries. Results showed that the application of a magnetic field significantly enhanced heat transfer performance, with a maximum Nusselt number enhancement of 230%. Moreover, it was shown that greater magnetic field intensities were associated with elevated friction factors, whereas friction factors exhibited a declining trend as Reynolds numbers increased. The thermal enhancement factor initially increased with Reynolds numbers, but declined after reaching a peak. However, higher magnetic field strengths mitigated this decline, intensifying heat transfer enhancement effects reaching a maximum of 2.18 at 2000G magnetic field. These findings provide quantitative insights into the effectiveness of magnetic fields in enhancing heat transfer in Fe3O4–TiO2 hybrid nanofluids.